Study of the profile of the neurotrophin BDNF in new leprosy cases before, during and after multidrug therapy - Rosane Dias Costa; Vanessa Amaral Mendonça; Rachel Adriana Penido; Sandra Lyon; Ana Maria Duarte Dias Costa; Marina Dias Costa; Fábio de Souza Terra; Thales Lage Bretas; Carlos Maurício de Figueiredo Antunes; Antônio Lúcio Teixeira (Arquivos de Neuro-Psiquiatria)
Brain-derived neurotrophic factor (BDNF) is a neurotrophin involved in the survival of neurons and growth and differentiation of dendrites and axons. The purpose of the present study was to evaluate plasma levels of BDNF of leprosy patients at different stages of multidrug therapy (MDT) in comparison with non-infected individuals. Plasma levels of BDNF were measured by ELISA in 30 healthy controls and 37 leprosy patients at diagnosis, during and after MDT. Plasma levels of BDNF tended to be higher in control subjects in comparison with leprosy patients, but this difference does not reach statistical significance. Interestingly, BDNF levels changed following MDT, achieving statistical difference only at the 2nd dose of MDT. These results indicate that BDNF may not be a surrogate marker of leprosy infection and/or related neuropathy. Further research is needed to investigate the meaning of BDNF level changes following leprosy treatment.